Experimental study on flame combustion characteristics of large-bore marine diesel engine based on endoscopic technology - Yue Li; Bingbing Liu; Shizhen Qin; Weijie Chang; Quan Dong (Case Studies in Thermal Engineering, 2023)
Large-bore marine diesel engines have the characteristics of poor ignition performance and insufficient combustion in the cylinder. This work revealed the combustion and emission performance of large-bore marine diesel engines based on endoscopic visualization technology. The flame temperature and soot distribution were analyzed in radial and axial directions. Results show that the large-bore diesel engine has a poor combustion effect because of the large fuel injection quantity and insufficient fuel-air mixing effect in the cylinder. The temperature in the cylinder rises twice in the late stage of combustion. The average temperature rises by 3.8%, caused by the secondary ignition of part of the unburned diesel. In addition, the large-bore engine produces a large amount of soot due to an insufficient mixing effect. It can be observed from the radial flame visualization images that the propagation speed of the flame is slow. The time required for the flame to propagate to the wall at 50% load is reduced by 31% compared with 25% load. The downward movement of the piston causes the flame tumble flow in the cylinder, resulting in an apparent asymmetric structure of the flame development.